QUASI-ELASTIC PROTON KNOCKOUT PROCESS 7 6 Li(e,e p) He IN POTENTIAL CLUSTER MODEL - Burkova, N. A.; Zhaksybekova, K. A.; Kabytaev, Ch. Z.; Urazalin, A. A. (Recent Contributions to Physics, 2009)
The description of the quasi-elastic proton knockout (e,e p) process from 7Li nucleus within the cluster potential theory is reported. The factorization approximations in PWA calculations are under discussion as well as spectroscopic and dynamical characteristics obtained from experiment.